Building Consumer-Based Brand Equity in Retail Banks: A Quantitative Study On a Pakistani Star Bank - Afzal Ahmed; Suman Talreja; Hina Naz (ETIKONOMI, 2018)
Firms are striving to increase their brand equity that ultimately leads to an increase in profitability. The purpose of the study is to identify the causal relationship of endorser's credibility with Brand credibility and its meditating role on consumer-based brand equity in the banking sector of Pakistan. 384 active HBC account holders taken as the sample and data collected through a comprehensive questionnaire. Correlation and regression analysis were conducted to test the factors of attractiveness, expertise, trustworthiness, and popularity on Brand credibility and further its effect on Brand equity. The results suggest that in banking sector firm Expertise of endorser is the most significant factor followed by trustworthiness and popularity that influence brand credibility and attractiveness does not have any impact on brand credibility. The study provides an understanding of brand building strategy, and it also highlights a clear brand differentiation strategy for bank brands.DOI: 10.15408/etk.v17i2.6728